We gather together : a nation divided, a president in turmoil, and a historic campaign to embrace gratitude and grace - Kiernan, Denise (Dutton, an imprint of Penguin Random House LLC, 2020)
"From the New York Times bestselling author of The Last Castle and The Girls of Atomic City comes the fascinating story of America's national day of thanks and of the tenacious and inspiring Sarah Josepha Hale, a nineteenth-century woman who made establishing this holiday her life's mission-one brought to fruition by the wise support of Abraham Lincoln"--